Role of Serum Vascular Endothelial Growth Factor (VEGF) as a Potential Biomarker of Response to Immune Checkpoint Inhibitor Therapy in Advanced Melanoma: Results of a Pilot Study - Khattak, Muhammad A.; Abed, Afaf; Reid, Anna L.; McEvoy, Ashleigh C.; Millward, Michael; Ziman, Melanie; Gray, Elin S. (Frontiers in Oncology, 2020)
Background: The development of biomarkers predictive of response to immune checkpoint inhibitor (ICI) therapies in advanced melanoma is an area of great interest in oncology. Our study evaluated the potential role of serum vascular endothelial growth factor (VEGF) as a predictive biomarker of clinical benefit and response to treatment with ICIs. Methods: Pre-treatment peripheral blood samples were obtained from advanced melanoma patients undergoing ICI therapy as monotherapy or in combination at two tertiary care hospitals in Western Australia. Serum VEGF levels were correlated with response to therapy and survival outcomes. Results: Serum VEGF samples were collected from a total of 130 patients treated with ICI therapy (pembrolizumab 73, ipilimumab 15 and ipilimumab/nivolumab combination 42). Median serum VEGF level was significantly higher in the non-responders (82.15 pg/mL) vs responders (60.40 pg/mL) in the ipilimumab monotherapy cohort (P<0.0352). However, no difference was seen in VEGF levels between non-responders and responders in pembrolizumab and ipilimumab/nivolumab treated patients. Conclusions: The results of our study confirm previous observations that that high pre-treatment serum VEGF levels in advanced melanoma patients may predict poor response to ipilimumab. However, serum VEGF is not predictive of outcome in patients treated with anti-PD-1 agents alone or in combination with ipilimumab. Keywords: Immunotherapy, vascular endothelial growth factor, melanoma, biomarker.